Role of an agro technique for the development of medicinal plant: Shalparni - Kiran, Usha; Pawar, G. B.; Vijay, Vijay; Thakur, Akanchha; Arya, J. C.; Venkateshwarlu, B.; Siddhamallayya, M.; Babu, G.; Srikant, N.; Acharya, R. N. (International journal of health sciences, 2022)
Vrikshayurveda a classical science of botanical field, this science deals with growth and development of plants. This science mainly suggests uses of Kunapa jala and Pancha gavya for the high productivity of crops. This concept works around organic farming for effective plant growth. Vrikshayurvedha mentioned Kunapajala as organic liquid manure which is a fermentation product and acts as plant nutrients. There are two types of Kunapajala mainly in practices viz; herbal and non-herbal which is prepared according to the procedures described in Vrikshayurvedha. Considering importance of this we planned a study to investigate role of Vrikshayurvedha concept for the development of medicinal plant; Shalparni. Present study investigated role of Kunapajala in the growth and % yield of plant Shalparni. This study observed that Kunapajala treatment offered best response with respect to root yield and soil physico-chemical parameters. Kunapajala increased plant yield quantitatively as well as qualitatively.